Anti‐retinal Autoantibodies in Hydroxychloroquine Eye Toxicity - Samuel D. Good; Grazyna Adamus; Michael B. Gorin; Jordan Jacquez; Jennifer Grossman; Isao Matsuura; Ashira Hasan; Brian Skaggs; Maureen McMahon (ACR Open Rheumatology)
Objective Autoimmune retinopathy and hydroxychloroquine (HCQ)‐related retinal toxicity share many similarities, raising the possibility autoimmunity plays a role in HCQ retinopathy. The objective of this study is to determine whether patients diagnosed with HCQ retinal toxicity are more likely to have circulating antiretinal autoantibodies (AAbs) compared to controls. Methods We tested plasma samples for the presence of anti‐retinal AAbs by immunoblotting in 270 patients with systemic lupus erythematosus (SLE) receiving HCQ. We then evaluated for the presence of HCQ retinal toxicity and other baseline risk factors for HCQ toxicity through chart review. Frequency of specific anti‐retinal AAbs in patients with HCQ retinal toxicity was compared to those with no retinal toxicity via multivariate logistic regression. Results Patients with HCQ retinal toxicity had a higher likelihood of testing positive for anti‐arrestin AAbs (60.7% vs 30.6%, P = 0.001) and anti–pyruvate kinase M2 AAbs (46.4% vs 28.1%, P = 0.05). Patients with HCQ eye toxicity also had a higher number of total anti‐retinal AAbs (mean 3.0 ± 2.40 vs 2.04 ± 1.7, P = 0.01). In multivariate analysis accounting for risk factors associated for HCQ eye toxicity, the presence of anti‐arrestin antibodies was associated with a 3.2‐fold increase in the odds of developing HCQ eye toxicity. Conclusion Anti‐retinal AAbs were more common in patients with SLE with HCQ retinal toxicity. When controlling for risk factors associated with HCQ toxicity, anti‐arrestin AAbs were associated with increased odds for the development of eye toxicity, suggesting a potential role for anti‐retinal AAbs as a biomarker of HCQ eye toxicity.